2010
DOI: 10.1111/j.1365-2567.2010.03341.x
|View full text |Cite
|
Sign up to set email alerts
|

Varying expression of four genes sharing a common regulatory sequence may differentiate rheumatoid arthritis from ageing effects on the CD4+ lymphocytes

Abstract: Summary The CD28 gene is similarly down‐regulated in CD4+ lymphocytes from both healthy elderly people and patients with rheumatoid arthritis (RA) because of impaired protein‐binding activity of the ‘α’ sequence in its promoter region. Other genes important for the CD4+ cell function may share that sequence and may be similarly regulated and affected. We searched GenBank for possible ‘α’ homologues and then compared transcriptional activities of the respective genes in the CD4+ cells of young and older healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Gendersegregated analyses with the GRS-tagged approach also confirmed the association of KL variants with LC in males. The present findings confirmed recent studies that have shown that the expression of the KL gene is extremely reduced in the CD4+ lymphocytes of patients with rheumatoid arthritis (Witkowski et al 2007), mostly in the cells of relatively younger patients (Soroczyńska-Cybula et al 2011), making them similar to the lymphocytes of healthy elderly in this aspect. Moreover, an impairment of B lymphopoiesis was demonstrated in mice homozygous for hypomorphic KL alleles and attributed to a defect in the "microenvironment" in the bone marrow (Okada et al 2000).…”
Section: Discussionsupporting
confidence: 92%
“…Gendersegregated analyses with the GRS-tagged approach also confirmed the association of KL variants with LC in males. The present findings confirmed recent studies that have shown that the expression of the KL gene is extremely reduced in the CD4+ lymphocytes of patients with rheumatoid arthritis (Witkowski et al 2007), mostly in the cells of relatively younger patients (Soroczyńska-Cybula et al 2011), making them similar to the lymphocytes of healthy elderly in this aspect. Moreover, an impairment of B lymphopoiesis was demonstrated in mice homozygous for hypomorphic KL alleles and attributed to a defect in the "microenvironment" in the bone marrow (Okada et al 2000).…”
Section: Discussionsupporting
confidence: 92%
“…It is hypothesized that modified in vitro proliferation dynamics of these cells may be associated with their reduced levels of CD28 expression, earlier proven to be due to an indirect effect of TNFα on the CD28 gene promoter (Bryl et al, 2001). We have demonstrated that the ZNF334 gene promoter contains a sequence closely homologous to the TN-Fα-responsive sequence in the promoter of CD28 gene (Soroczynska-Cybula et al, 2011). These observations led to the hypothesis that also the expression of ZNF334 is controlled by TNFα.…”
Section: Introductionmentioning
confidence: 79%
“…Zinc finger proteins are thought to function as either positive or negative regulators of expression of other genes (Urrutia, 2003;Soroczynska-Cybula et al, 2011). Recently, a novel function has been proposed for two related zinc finger proteins, ZNF91 and ZNF93, suggested to have evolved to suppress retrotransposons (Jacobs et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations